(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Salwiyah, Purnama MF, Syukur. 2022. Ecological index of freshwater gastropods in Kolaka District, Southeast Sulawesi, Indonesia. Biodiversitas 23: 3031-3041. Kolaka District is one of the existing centers of high freshwater gastropod diversity in Southeast Sulawesi Province, Indonesia. more than 30 species of inland gastropods occupy this area and some of them (species) are used by local communities as food (daily consumption). This research was conducted for 4 months, namely January-April 2021 in Kolaka District, Southeast Sulawesi, Indonesia. The purpose of this study was to determine the ecological index (abundance, diversity, evenness, species richness, dominance, and distribution pattern) of the inland gastropod community in Kolaka. The sampling location of gastropods was determined qualitatively using the purposive sampling method and sampling using a simple random sampling technique (Quantitative based). Gastropod samples were collected manually (hand picking) using a paralone pipe (3.5 inches), Sieve (1 mm), and Gloves. The total gastropod sample obtained during the study was 1929 individuals consisting of 9 families, 19 genera, and 33 species. The average abundance of the gastropod population reached 96.45 ind./m2 and the abundance of gastropod species ranged from 0.75-15.05 ind./m2. Overall, the results of the gastropod ecological index analysis showed a stable condition, where the diversity of gastropod species was categorized as high (H’: 3.20), moderate evenness (E: 0.90), and high species richness (R: 4.23), dominant dominance. showed that there were no dominant species (C: 0.1) and the distribution of gastropods showed a clumped pattern (Ip: 0.01). Empirically the ecological index data is a scientific justification related to the sustainability of inland water ecosystems or a description of the current freshwater homeostasis system in Kolaka.